Quadratic Equation (x + 4)(x – 1) = 0
|languages||English, Hindi, Malayalam|
I have completed +2. but all ur doubts abt maths could be ANSWERED.
Experience: 0 years
Often, the simplest way to solve "ax2 + bx + c= 0" for the value of x is to factor the quadratic, set each factor equal to zero, and then solve each factor. But sometimes the quadratic is too messy, or it doesn't factor at all, or you just don't feel like factoring. While factoring may not always be successful, the Quadratic Formula can always find the solution.
To find the soln:
For ax2 + bx + c = 0, the value of x is given by:
or you can factorise.
Consider an example
x2 + 3x – 4 = 0
which is of the form
ax2 + bx + c= 0
in order to factorise all types of quadratic we have to convert in the std form
here sum = 3 and product = -4.
then we have to think 2 numbers whose product is -4 and sum is 3
the numbers are -1 and 4 whose
sum=3 and product=-4
(x + 4)(x – 1) = 0
x=-4 and x=1 on equating with zero.